2021
DOI: 10.1111/add.15571
|View full text |Cite|
|
Sign up to set email alerts
|

National trends in population rates of opioid‐related mortality, hospitalization and emergency department visits in Canada between 2000 and 2017. A population‐based study

Abstract: Background and aimsExisting assessments of the time-trends of opioid-related mortality, hospitalization and emergency department visits in Canada have relied mainly on provincial databases, while national assessments generally do not provide information before 2016. We aimed to estimate Canadian national time trends in opioid-related mortality from 2000 to 2017 and opioid-related hospitalization and emergency department visits between 2000 and 2012.Design Retrospective cohort study. Setting and participants Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…We previously published a similar network meta-analysis that assessed the effectiveness of oral NSAIDs and paracetamol 33. With the ever increasing use of opioids in osteoarthritis treatment and the recommendation from recent guidelines to consider topical NSAIDs as a first line treatment, we expanded the previous review to also include these interventions to assess their comparative effectiveness and safety 67891618. We also included safety outcomes in the current review, which were not reported in our previous review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously published a similar network meta-analysis that assessed the effectiveness of oral NSAIDs and paracetamol 33. With the ever increasing use of opioids in osteoarthritis treatment and the recommendation from recent guidelines to consider topical NSAIDs as a first line treatment, we expanded the previous review to also include these interventions to assess their comparative effectiveness and safety 67891618. We also included safety outcomes in the current review, which were not reported in our previous review.…”
Section: Discussionmentioning
confidence: 99%
“…17 Between 2000 and 2017, opioid related mortality increased by 593% in Canada. 18 Despite this evidence, and international concerns about the devastating potential for chemical dependency, 7 19 opioids remain among the most prescribed drugs for osteoarthritis pain in the UK, the US, Canada, and Australia, even though safer treatments with stronger analgesic effects are available. 9 20-23 Previous systematic reviews have reported the effectiveness of NSAIDs and opioids to treat osteoarthritis pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While prescribed opioid use has been shown to be associated with increased mortality, hospitalizations, and ED visits [ 3 , 4 ], the effect on cardiovascular outcomes remains controversial [ 11 ]. In our study, we demonstrated an increased hazard of IHD-hospitalizations associated with prescribed opioids regardless of OSA status.…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing opioid epidemic in North America [ 1 ] has led to an increased frequency of adverse opioid-related outcomes, such as higher rates of emergency department (ED) visits, hospitalization, and mortality [ 2 , 3 ]. Although the current epidemic and adverse outcomes are no longer being driven by prescribed opioids for therapeutic use [ 4 , 5 ], safe prescribing of opioids is still important [ 6 ].…”
Section: Introductionmentioning
confidence: 99%